Novel multiplex-PCR for rapid detection of Bacillus anthracis spores present in soils of Sirajganj district in Bangladesh - Nazir, KHMNH; Hassan, J; Chowdhury, SMZH; Rahman, MB (Progressive Agriculture, 2015)
Bacillus anthracis spores were isolated and detected from soil samples (n=72) using multiplex-PCR method. The bacteria were isolated and primarily identified as Bacillus anthracis using selective Polymyxin B - Lysozyme - EDTA - Thallous acetate agar. A multiplex-PCR method targeting three genes; rpoB of genome, pag of pX01 and cap of pX02 was done to confirm the isolated bacteria. Among 72 soil samples, the viable B. anthracis spores could be extracted from 14 (19.44%) samples. However, both pX01 and pX02 plasmids were harbored in 5 (6.94%) isolates. On the other hand, pX01 and pX02 was present in 8 (57.14%) and 11 (78.57%) isolates, respectively. This two-step-method was found to be easy, accurate and rapid in identification of B. anthracis spores from soil samples and to identify the toxigenic plasmids present in this bacterium. Progressive Agriculture 26:67-70, 2015